General education institution readiness of students with special needs into the mainstream realizing inclusive education policy - Rozenfelde, Mārīte; Orska, Rita; Kondrova, Aija (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The article deals with the historical process of integration/inclusion of children with special needs into mainstream educational establishments in Latvia since 1998 when the pedagogical staff in Latvia was introduced the term “inclusive education” broader for the first time and there were offered practical recommendations for school and class work; afterwards some educational establishments started implementing inclusive education; the current situation regarding inclusion/integration of children with special needs in mainstream educational establishments is evaluated in the questionnaire provided to the heads of educational establishments. There are provided the data of the provided questionnaires regarding the readiness of mainstream schools in Latgale and Vidzeme regions and real situation in the integration of children with special needs.